Evaluasi Efektifitas Proses Pre-Turning Dengan Penerapan Total Productive Maintenance Pada PT Apcb - Noviardi Noviardi; Nofriani Fajrah (LPPM Universitas Putera Batam, 2020)
Machinery or production equipment is one of the assets owned by a company thatrequires effective maintenance in order for the company to continue to be productive.Problem encountered is found the machine / production equipment that can not operateproperly, causing the engine breakdown is increasing. One step that can be taken by the company to be able to determine the level of effectiveness of machinery and equipment production by measuring the level of Overall Equipment Effectiveness (OEE). The purpose of this study is to evaluate the effectiveness of pre-turning process in maintenance activities to improve productivity of PT APCB, to identify causes of non-optimal maintenance activities at PT APCB, and to propose improvements for maintenance effectiveness at PT APCB. One approach that can be applied by PT APCB is by applying Total Productive Maintenance (TPM). Based on the calculation results, obtained the average OEE value in 2016 was 67,45%. The lowest OEE value in the Pre-Turning process in 2016 was in February at 48.31%, while for the highest OEE in September was 83.23%. This is caused by the bar feeder problem with the highest request frequency value so that the low effectiveness of the Pre-turning process is indicated by the low value of OEE. Proposed improvement for maintenance effectiveness at PT APCB is to apply TPM better by always controlling the level of OEE.